Analisis Pengaruh Harga dan Kualitas Produk terhadap Keputusan Pembelian Pakaian Bekas Pasar Perumnas Way Halim (Studi Kasus pada Thrift Bylels) - Wahyuni, Lela Putri; Habiburahman (Jurnal EMT KITA, 2025)
The purpose of this study was to find out how the influence of buying used clothes at thrift bylels Pasar Perumnas Way Halim has on the price and quality of the product. This study uses quantitative research with a sample of fifty thrift bylels used clothing store customers. SPSS version 26 is used for research results. In this study, descriptive analysis and multiple linear regression were used to test the validity, reliability, coefficients and determination, partial and simultaneous tests on the data. The research findings show that purchasing decisions are influenced by product quality and price.